Factors that satisfy the Takaful product customers among Melaka Residence / Mohd Farhat Aziz - Aziz, Mohd Farhat (Faculty of Business and Management, 2019)
Currently, Takaful industry is increasing a little bit compared to the previous years. Takaful company are always deal with customer and need to maintain their management in order to fulfil customer satisfaction in Takaful. The purpose of this study is to measure the customer satisfaction of Takaftll products and services. The dependent variable is customer satisfaction. While the independent variables are religiosity, services quality, product innovation, distributive fairness and price contribution. This study surveyed 200 customer who have any plan of Takaful products and services in Malaysia and specific in are Melaka town. In this study we used primary data which the questionnaire will distribute in the form of Google Doc through Whatsapp or Facebook or share in the group. We also distribute by hand among the any Takaful customers. In the research methodology, the descriptive analysis, reliability and validity test and regression analysis will be conducted using SPSS 22 package. From the result, we found that religiosity, service quality and fairness distribution are significant.